Urban Sprawl, Suburbanization, and Informal Sector in Western Suburb Area-Malang City-East Java - Satti Wagistina; Agus Suman; Antariksa Antariksa; Bagyo Yanuwiadi (Wacana Journal of Social and Humanity Studies, 2017)
This study aimed at analyzing the impact of urban sprawl towards suburbanization and informal sector in western suburb area of Malang City. Mix method was employed by incorporating both quantitative and qualitative approaches. A quantitative approach was employed to investigate the urban sprawl by utilizing SIG method integrated with remote sensing by the indicators of built-up land in 1995,2000, 2003, 2010, and 2015. A qualitative approach was aimed at detecting the stages of suburbanization in the western suburb area of Malang City.The location to conduct the study was determined by means of purposive sampling. The data were collected through semi-structured interview with the recruited 50 natives and 50 migrants. The in-depth interviews were conducted with some community figures.This current study has found that suburbanization in the western suburb area of Malang City comprises three stages, namely: 1) pre-suburbanization occurred until 1990; 2) the first stage of suburbanization occurred in the early 1990s; and 3) the second stage of suburbanization occurred in 2000s. This study has also uncovered that suburbanization affects the growth of an informal sector that has eroded the strategic role of the agricultural sector, and thus the area grows as peri-urban. Eventually, urban sprawl, suburbanization, and the growth of informal sector result in the agricultural involution and emerging poverty phenomenon.